Global transcriptome analysis of porcine oocytes in correlation with follicle size - Gad, Ahmed; Nemcova, Lucie; Murin, Matej; Kinterova, Veronika; Kanka, Jiri; Laurincik, Jozef; Benc, Michal; Pendovski, Lazo; Prochazka, Radek (Molecular reproduction and development, 2020)
Although our knowledge regarding oocyte quality and development has improved significantly, the molecular mechanisms that regulate and determine oocyte developmental competence are still unclear. Therefore, the objective of this study was to identify and analyze the transcriptome profiles of porcine oocytes derived from large or small follicles using RNA high-throughput sequencing technology. RNA libraries were constructed from oocytes of large (LO; 3-6 mm) or small (SO; 1.5-1.9 mm) ovarian follicles and then sequenced in an Illumina HiSeq4000. Transcriptome analysis showed a total of 14,557 genes were commonly detected in both oocyte groups. Genes related to the cell cycle, oocyte meiosis, and quality were among the top highly expressed genes in both groups. Differential expression analysis revealed 60 up- and 262 downregulated genes in the LO compared with the SO group. BRCA2, GPLD1, ZP3, ND3, and ND4L were among the highly abundant and highly significant differentially expressed genes (DEGs). The ontological classification of DEGs indicated that protein processing in endoplasmic reticulum was the top enriched pathway. In addition, biological processes related to cell growth and signaling, gene expression regulations, cytoskeleton, and extracellular matrix organization were among the highly enriched processes. In conclusion, this study provides new insights into the global transcriptome changes and the abundance of specific transcripts in porcine oocytes in correlation with follicle size.
Keywords: prasata; Swine; transkriptom; oocyty; vývojová regulace genové exprese; High-Throughput Nucleotide Sequencing; Gene Expression Regulation, Developmental; Gene Regulatory Networks; signální transdukce; Transcriptome; polymerázová řetězová reakce s reverzní transkripcí; stanovení celkové genové exprese; Signal Transduction; Gene Expression Profiling; genové regulační sítě; oogeneze; Animals; ženské pohlaví; ovariální folikul; zvířata; vysoce účinné nukleotidové sekvenování; Reverse Transcriptase Polymerase Chain Reaction; Ovarian Follicle; Female; Oogenesis; Oocytes